2019
DOI: 10.1002/humu.23916
|View full text |Cite
|
Sign up to set email alerts
|

Mutation update for theNR5A1gene involved in DSD and infertility

Abstract: Nuclear receptor subfamily 5 group A member 1 (NR5A1), also named steroidogenic factor 1, is an essential transcription factor that regulates a number of target genes crucial for normal reproductive physiology and endocrine function. It is encoded by NR5A1 gene and is expressed in high doses mainly in steroidogenic tissues, where it controls several steps of adrenal and gonadal development. NR5A1 mutations are associated with a wide phenotypic spectrum of disorders/differences of sex development (DSD), a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 102 publications
(77 reference statements)
5
70
0
Order By: Relevance
“…However, the precise mechanism by which NR5A1 action fails and leads to DSD is not fully understood, nor has an explanation been provided for the wide-ranging phenotypes associated with different and, in some cases identical, NR5A1 variants. This is despite numerous studies attempting to resolve this question by analyzing defective NR5A1 function at steroidogenic target promoter (such as CYP11A1, CYP17A1, and CYP19A1) or sex differentiation genes (AMH and INSL3) [57].…”
Section: Nr5a1 (Sf1) and Wt1: Old Genes New Mechanismsmentioning
confidence: 99%
“…However, the precise mechanism by which NR5A1 action fails and leads to DSD is not fully understood, nor has an explanation been provided for the wide-ranging phenotypes associated with different and, in some cases identical, NR5A1 variants. This is despite numerous studies attempting to resolve this question by analyzing defective NR5A1 function at steroidogenic target promoter (such as CYP11A1, CYP17A1, and CYP19A1) or sex differentiation genes (AMH and INSL3) [57].…”
Section: Nr5a1 (Sf1) and Wt1: Old Genes New Mechanismsmentioning
confidence: 99%
“…Thus, our study, similar to others [41][42][43][44], was not able to demonstrate a disease-causing effect leaving genotype-phenotype correlation for NR5A1 variants unsolved. Many patients with variants in NR5A1 have been described with broad phenotypes ranging from severe 46,XY DSD to unvirilized males with/without adrenal failure, 46,XX with ovarian insufficiency, 46,XX with ovotesticular DSD, and healthy carriers [45]. On the other hand, it has also been shown that SF-1 has an extraordinary network of regulators, modulators, and target genes [46][47][48].…”
Section: Hts In a Second Approach To Detect Digenic Or Oligogenic Orimentioning
confidence: 99%
“…We therefore performed a WES analysis in four of these 46,XY DSD patients with heterozygous NR5A1 gene defects [13] in search for additional genetic hits explaining the phenotypic variability described in patients with NR5A1 mutations [45]. For specific bioinformatic analysis, candidate genes for DSD and genes related to NR5A1 were collected from the literature and databases including known and potential candidate genes.…”
Section: Hts In a Second Approach To Detect Digenic Or Oligogenic Orimentioning
confidence: 99%
“…Loss of functions mutations of NR5A1 lead to complete adrenal and gonadal agenesis, alterations in virilization, and retention of Müllerian ducts in XY mice [Sadovsky et al, 1995]. In humans, NR5A1 gene variants are responsible for a wide spectrum of phenotypes, including adrenal insufficiency, disorder of sex development (DSD), and primary ovarian insufficiency [Achermann et al, 1999[Achermann et al, , 2002Lourenço et al, 2009;Suntharalingham et al ., 2015;Robevska et al, 2018;Fabbri-Scallet et al, 2020]. In addition, mutations in the NR5A1 gene have been found in males with bilateral anorchia, isolated hypospadias, male infertility, and in some subjects with adrenal tumors and endometriosis [reviewed in Ferraz-de-Souza et al, 2011;Fabbri-Scallet et al, 2020].…”
mentioning
confidence: 99%
“…In humans, NR5A1 gene variants are responsible for a wide spectrum of phenotypes, including adrenal insufficiency, disorder of sex development (DSD), and primary ovarian insufficiency [Achermann et al, 1999[Achermann et al, , 2002Lourenço et al, 2009;Suntharalingham et al ., 2015;Robevska et al, 2018;Fabbri-Scallet et al, 2020]. In addition, mutations in the NR5A1 gene have been found in males with bilateral anorchia, isolated hypospadias, male infertility, and in some subjects with adrenal tumors and endometriosis [reviewed in Ferraz-de-Souza et al, 2011;Fabbri-Scallet et al, 2020]. So far, a clear genotypephenotype correlation has not been established yet, and a polygenic inheritance might explain the broad phenotypic variability associated with NR5A1 gene mutations [Ma-zen et al, 2016;Camats et al, 2018].…”
mentioning
confidence: 99%